Transgenerational inheritance of paternal neurobehavioral phenotypes: stress, addiction, ageing and metabolism - Yuan, Ti-Fei (2015)
Epigenetic modulation is found to get involved in multiple neurobehavioral processes. It is believed that different types of environmental stimuli could alter the epigenome of the whole brain or related neural circuits, subsequently contributing to the long-lasting neural plasticity of certain behavioral phenotypes. While the maternal influence on the health of offsprings has been long recognized, recent findings highlight an alternative way for neurobehavioral phenotypes to be passed on to the next generation, i.e., through the male germ line. In this review, we focus specifically on the transgenerational modulation induced by environmental stress, drugs of abuse, and other physical or mental changes (e.g., ageing, metabolism, fear) in fathers, and recapitulate the underlying mechanisms potentially mediating the alterations in epigenome or gene expression of offsprings. Together, these findings suggest that the inheritance of phenotypic traits through male germ-line epigenome may represent the unique manner of adaptation during evolution. Hence, more attention should be paid to the paternal health, given its equivalently important role in affecting neurobehaviors of descendants.